Bioactive extracts from the industrial byproduct of passion fruit promote better glycemic control in an adjuvant treatment with insulin and prevent kidney and heart damage in rats with type 1 Diabetes mellitus - Bárbara Cabral; Ony Araújo Galdino; Iago de Souza Gomes; Jovelina Samara Ferreira Alves; José Ivan Marques; Karla Simone Costa de Souza; Rodrigo Moreira da Silva; Bento João Abreu; Norberto Peporine Lopes; Silvana Maria Zucolotto; Adriana Augusto de Rezende (Journal of Functional Foods)
The study investigated the potential benefits of passion fruit peel extracts (PFAE and PFHE), derived from Passiflora edulis fo. flavicarpa, for Type 1 Diabetes mellitus (T1DM). Extracts were produced using eco-friendly solvents and evaluated in a T1DM chronic model. Acute toxicity tests showed the extracts (2000 mg/kg, orally) were safe. Liquid chromatography coupled to triple quadrupole mass spectrometry (LC-QqQ-MS/MS) identified five C-glycosylated flavonoids (vicenin-2, orientin, isoorientin, vitexin, isovitexin) in the extracts. Adjuvant treatment with extracts alongside insulin significantly improved glycemic control over 60 days compared to insulin alone (p < 0.05). Furthermore, extracts protected against renal fibrosis and maintenance of the levels of inflammatory markers, such as myeloperoxidase, in the hearts and kidneys of diabetic rats. These findings suggest passion fruit peel extracts could enhance long-term T1DM management by improving glycemic control and preventing organ damage, potentially inspiring the development of new food or pharmaceutical products with beneficial actions for T1DM.